Forecasting Produksi Kayu Bulat di Indonesia - Aniisa Rizqi; Hanif Palupi; Novantia Novantia; Bayu Rhamadani Wicaksono; RR. Nila Indrasari (Politeknik Statistika STIS, 2022)
For next 15 years, the SDGs aim to end poverty, hunger, and realize sustainable development in social, economic, and environmental dimensions. Indonesia that has production forests is an important contributor for the SDGs achievement, particularly in the economic (Goal 12) and environmental dimensions (Goal 15). The SDGs implementation was hampered by the Covid-19 pandemic in 2020 so the Indonesian economic growth declined. On the other hand, the agriculture, forestry, and fisheries sectors continued to grow positively. Currently, SDGs are the main reference for determining national government programs and policies and data is the primary key for the government to achieve sustainable forestry. However, there is no data on the potential growth of Indonesian logs production so this study aims to forecasting logs production in Indonesia using ARIMA. The forecasting results with ARIMA (3,1,1) as the best ARIMA model show that the 2021Q1-2022Q4 data is slightly volatile with an upward trend.